GLOBALISASI SEBAGAI WACANA DAN FENOMENA: KAJIAN DESKRIPTIF ANALITIS TERHADAP EKSISTENSI LEMBAGA PENDIDIKAN ISLAM DI ERA GLOBALISASI - Ikbal, Muhammad; Hidayatullah; Bahrudin, Andre; Harto, Kasinyo; Amilda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Globalization as a complex phenomenon has influenced various aspects of life, including the existence of Islamic education institutions. This article aims to critically analyze the influence of globalization on Islamic education institutions, both as a discourse and a phenomenon. The research method used is descriptive-analytic, involving the decomposition and interpretation of data to understand the impact of globalization. The results of the study show that globalization presents challenges such as global competition and the potential for identity erosion, but also opens up opportunities such as access to global resources and the development of innovative curricula. It is concluded that Islamic education institutions need to adopt adaptive and innovative strategies to remain relevant and make a positive contribution in the era of globalization.